Enhancing Customer Satisfaction: The Impact of Experience and Value in PLN Mobile App - Sholahudin, Ridwan; Sari, Rini Mulyani (International Journal of Education, Management, and Technology, 2025)
This study aims to analyze the effect of customer experience (X1) and customer value (X2) on customer satisfaction (Y) at PT PLN ULP Kosambi. This research uses a quantitative method with multiple linear regression analysis to examine the relationships between variables. Data were collected through questionnaires distributed to 95 respondents, who are customers of PT PLN ULP Kosambi. The results indicate that customer experience (X1) and customer value (X2) have a significant effect on customer satisfaction (Y). The coefficient of determination (R²) shows a contribution of 66.1% from customer experience and customer value on customer satisfaction. The F-test shows that both customer experience and customer value significantly affect customer satisfaction together. Based on the t-test results, both independent variables also have a positive and significant effect on customer satisfaction individually. The implications of this study highlight the importance of improving customer experience and perceived value to achieve optimal customer satisfaction.